RELATIONSHIPS TO PERSONAL NAMES IN THE UZBEK DIALECTS OF SOUTHERN KARAKALPAZISTAN - Karimboyeva Charos (International Journal of Innovations in Engineering Research and Technology, 2023)
In this article, it is possible to observe cases where names become nicknames based on various connections and characteristics, in addition to the fact that human names used in dialects become nicknames and nicknames come with a name, and become active at the level of a name.